Efficient estimation of alternative pricing models for currency futures contracts - SEQUEIRA, J. M. (Institutional Knowledge at Singapore Management University, 1999)
The Risk Premium and Cost-of-Carry models regarding the pricing of Australian dollar futures contracts traded on the International Monetary Market of the Chicago Mercantile Exchange are estimated and compared. Cointegrating relationships among the Australian dollar spot and futures prices, and US and Australian risk-free rates of interest, suggest an error-correction representation for the Risk Premium model, and two alternative error-correction formulations for the Cost-of-Carry model. Two significant structural breaks in the futures price series permit estimation of appropriate models for the full sample in the presence of these breaks, for the full sample without explicitly modelling the breaks, and for various sub-samples created by these structural breaks. The Risk Premium and Cost-of-Carry formulations are estimated for all sample sets, the models obtained are found to be statistically adequate, and the qualitative results are reasonably robust across different sample sets for both models.